The Influence of Organizational Commitment, Implementation of Accounting Information System and Workplace Environment to The Performance of Work Unit - Ratna Djuwita; Roebiandini Soemantri; Gia Kardina Prima (Journal of Accounting Auditing and Business, 2018)
This study aims to obtain empirical evidence on the influence of organizational commitment, implementation of accounting information system and workplace environment affected the performance of the work unit at the Ministry of Public Works and Housing. This study method used survey research with the target population studied is the unit of echelon II work unit that prepares the report of the Government Institution Performance unit (Laporan Kinerja Instansi Pemerintah) in the Ministry of Public Works and Housing. This research design used descriptive approach by using questionnaires to collect data on 122 respondents in 67 work units consists of (1) head of work unit  (2) administrator official (3) supervisor officer (4) staff, this research hypothesis test using multiple regression analysis models. The results show that (1) organizational commitment positively affected to the performance of work unit at the Ministry of Public Works and Housing (2) Implementation of Accounting Information System positively affected to the performance of work unit at the Ministry of Public Works and Housing (3) Work environment positively affected at the Ministry of Public Works and Housing.